Synthesis, Characterization and Study the Biological Activity ofnew Derivatives of 1,3- orazepine containing 1,2,4-Triazoloe ring - A. Yass, Iman; A. Jabar, Salwa; H. Jumaa, Fawzi (Tikrit Journal of Pharmaceutical Sciences, 2023)
Compound [1] is prepared from Esterificition of 4-Nitro benzoic acid. It has been reacted with hydrazine to get compound [2]. 3,5-bis (4-Nitro phenyl)-4-amino -1,2,4-triazole [3] has been synthesized by melting of 4-Nitro benzoic acid hydrizide to cretin temperature. The new series of Schiff bases [4a-f] have been syntheised by reacting compound [3] with different benzaldehydes., These derivatives shows ring closer reaction with phathalic anhydride to obtain 1.3- Oxazepine derivatives [Sa-f]. The syntheised compound were characterized by (IR.UV) spectra, melting points the above reaction were followed by TLC. The biological activities are studied against four different kinds of bacteria .